The analysis of health research system evaluation in medical sciences universities. - Sh Djalalinia; N Peykari; P Owlia; M Baradaran Eftekhari; E Habibi; K Falahat; Sh Mojarrab; H Malekafzali; M Ghanei (Tehran University of Medical Sciences, 2013)
Based on Iran by 2025 defined vision, we must to receive the first grade of science position in south western Asian region. Thus we need to have a comprehensive evaluation program.A comprehensive WHO Health Research System Analysis (HRSA)- based evaluation system was developed to evaluate the HRS in Iran. This article has explored the results of the five-year evaluation (2003-2008) and aims to introduce this method to other developing countries. Here we explore the results of research performance evaluation from 2002 to 2010 and by comparing the results with previous available information, we reveal the probable role of this method in research promotion and proposed approach to facilitate and expedite achieving the prospects for goals of health research based on the visions of Iran by 2025.All of the indicators of stewardship and capacity building axes are received to their predefined levels. Moreover all of the medical science university research policies are based on their strategic plannings which are extracted from national visions of Iran by 2025. Most of the predefined goals in knowledge production domain had a significant grow trend but for more growth for commitments they should be closely follow.We developed an HRS-based comprehensive evaluation program to our national vision as well as our regional and international research competition.